2023
DOI: 10.56855/ijcse.v2i1.252
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Significance of Vocabulary in Fostering ESL/EFL Students' Writing Skills: An Empirical Study

Abstract: Writing skill is an important tool for academic success of any professional individual.  This paper aims to analyze the indispensability of having vocabulary knowledge which in turn helps foster ESL/EFL students’ writing performance for their academic success. To this end, the researcher has gathered the past research papers in order to collect the important details of the relationship between vocabulary and writing skills. Moreover, this paper presented theoretical perspectives of vocabulary and writing. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In this case, repeating reading several times, notably by voice, ameliorates the students' Speaking Skills and enriches vocabulary mastery. However, (Dhuli et al, 2023) ix found the technique of Reading Aloud has no meaningful effect on students' vocabulary learning (Dhuli et al, 2023 x ;Arafah et al, 2023 xi ), Reading Aloud, if it is frequently undertaken, is a speaking practice and beneficial to vocabulary learning. This activity is significant as an effort to familiarize the pronunciation of English words.…”
Section: Exploring the Importance Of The Problemmentioning
confidence: 99%
“…In this case, repeating reading several times, notably by voice, ameliorates the students' Speaking Skills and enriches vocabulary mastery. However, (Dhuli et al, 2023) ix found the technique of Reading Aloud has no meaningful effect on students' vocabulary learning (Dhuli et al, 2023 x ;Arafah et al, 2023 xi ), Reading Aloud, if it is frequently undertaken, is a speaking practice and beneficial to vocabulary learning. This activity is significant as an effort to familiarize the pronunciation of English words.…”
Section: Exploring the Importance Of The Problemmentioning
confidence: 99%